2001
DOI: 10.1096/fj.00-0247com
|View full text |Cite
|
Sign up to set email alerts
|

Specificity, diversity, and convergence in VEGF and TNF‐α signaling events leading to tissue factor up regulation via EGR‐1 in endothelial cells

Abstract: Tissue factor (TF) has been shown to be up-regulated in endothelial cells by the inflammatory cytokine tumor necrosis factor alpha (TNF-alpha) as well as by the main angiogenic factor VEGF. Since both stimuli induce the transcription factor EGR-1, which is critically involved in TF gene regulation, we used EGR-1-dependent TF induction as a model to identify potential cross-talks between the various signal transduction cascades initiated by VEGF and TNF-alpha. The data show that at the MAP kinase level, VEGF ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
182
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(193 citation statements)
references
References 73 publications
9
182
2
Order By: Relevance
“…and NFAT) [27][28][29][30]. In cancer cells, the effects of oncogenic EGFR on TF are mediated through an NFκB dependent mechanism [10], as well as by processes involving AP-1 and c-Jun Nterminal kinase (JNK) activation [12].…”
Section: Discussionmentioning
confidence: 99%
“…and NFAT) [27][28][29][30]. In cancer cells, the effects of oncogenic EGFR on TF are mediated through an NFκB dependent mechanism [10], as well as by processes involving AP-1 and c-Jun Nterminal kinase (JNK) activation [12].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established an important role for MEK/MAP kinase in mediating Egr-1 expression in response to other growth factors and hormones (Hodge et al, 1998;Tsai et al, 2000;Mechtcheriakova et al, 2001;Wu et al, 2002). This signaling pathway regulates Egr-1 gene expression mainly through activation of the SREs in the human Egr-1 promoter.…”
Section: Hgf Stimulates Fibronectin Expression In Melanomas C Gaggiolmentioning
confidence: 99%
“…Major signals induced by VEGF via VEGFR-2 in endothelial cells include activation of the phosphoinositol 3-kinase/PKB and phospholipase C-␥/PKC pathways (4,5). Whereas activation of PKB has been primarily implicated in cell survival (6), recent in vitro studies have shown that VEGF treatment of endothelial cells leads to a PKC-dependent activation of the MEK/ERK module of MAP kinases resulting in a rapid up-regulation of the transcription factor EGR-1 (7,8), which has been associated with growth and differentiation of various cell types (9,10). Furthermore, EGR-1 is critically involved in the up-regulation of genes such as tissue factor (TF) (7,8), VEGF receptor-1 (VEGFR-1) (11,12), and urokinase-type plasminogen activator (uPA) (13).…”
mentioning
confidence: 99%
“…Whereas activation of PKB has been primarily implicated in cell survival (6), recent in vitro studies have shown that VEGF treatment of endothelial cells leads to a PKC-dependent activation of the MEK/ERK module of MAP kinases resulting in a rapid up-regulation of the transcription factor EGR-1 (7,8), which has been associated with growth and differentiation of various cell types (9,10). Furthermore, EGR-1 is critically involved in the up-regulation of genes such as tissue factor (TF) (7,8), VEGF receptor-1 (VEGFR-1) (11,12), and urokinase-type plasminogen activator (uPA) (13). These genes have been proposed to fulfill important functions for different aspects of vasculogenesis and angiogenesis (1,2,14).…”
mentioning
confidence: 99%